Effects of Lactoferrin-Fortified Formula on Acute Gastrointestinal Symptoms in Children Aged 12–32 Months: A Randomized, Double-Blind, Placebo-Controlled Trial - Motoki, Noriko; Mizuki, Masaru; Tsukahara, Teruomi; Miyakawa, Momoko; Kubo, Shutaro; Oda, Hirotsugu; Tanaka, Miyuki; Yamauchi, Koji; Abe, Fumiaki; Nomiyama, Tetsuo (Frontiers in Pediatrics, 2020)
Objective: We investigated the effects of lactoferrin (LF)-fortified formula on acute gastrointestinal and respiratory symptoms in children. Design: Randomized, double-blind, placebo-controlled trial. Setting and subjects: Children aged 12–32 months in Japan. Intervention: Intake of placebo or LF (48 mg/day)-fortified formula for 13 weeks. Primary endpoint: Prevalence of acute gastrointestinal respiratory symptom. Results: One hundred nine participants were randomized. Eight participants were lost to follow-up, withdrew consent, or were deemed inappropriate for the trial, with 101 participants receiving complete analyses (placebo group, n = 48; LF group, n = 53). Outcomes: The prevalence of acute gastrointestinal symptoms was significantly less in the LF group (22/53 [41.5%]) than in the placebo group (30/48 [62.5%], p = 0.046). The total number of days having acute respiratory symptoms was significantly lower in the LF group (9.0) than in the placebo group (15.0, p = 0.030). Harms: The rate of adverse events was similar between the groups. No adverse drug reactions were found. Conclusions: LF intake decreased the prevalence of acute gastrointestinal symptoms in children aged 12–32 months.